Toxic waste minimization in the printed circuit board industry - Nunno, T. (Pollution technology review, 1988)
Presents information on waste minimization practices in the printed circuit board and semiconductor manufacturing industries. Case studies conducted at six facilities evaluated the technical, environmental and cost impacts associated with the implementation of technologies for reducing the volume and toxicity of printed-circuit-board metals-containing sludges and solvent wastes.